Network Based High Speed Product Development - Lindgren, Peter (Taylor & Francis, 2017)
In the first decade of the 21st century product development in networks was predicted to be of ever-increasing importance to businesses of all sizes because of changes in markets, in technology, in networks, and in the competences of Businesses. The growth in new products' share of businesses' total turnover and earnings were increasing at an unprecedented speed. The entrepreneurial innovations and technological improvements had resulted in the increasingly fast development of new products and services. Businesses and industries in different countries became increasingly more linked and interdependent in networks with respect to materials, business operations and particularly product development to match the wants and needs of the global market environment to high speed product development. Businesses were therefore encountering increasingly dynamic market fragmentation, shrinking time in market, increasing product variety, demands of production to customer specifications, reduced product lifetimes, and globalization of production.Networks were vital because the competition is not business against business, but network against network. Networks are vital because an increasing part of product development was carried out in all types of networks containing physical, ICT, dynamic, and virtual networks. Speed and pressure on time in product development seemed to continue to increase because customer demands for new products seemed to continue to increase. However, a Business seldom possessed all needed competences, and managers saw product development based on networks as an important solution to meet the strong competition of the future global markets and the strong demand for innovation and innovativeness. The evolution of market demands and focus (required) on competencies of businesses could be characterized as a development from a focus on efficiency, to a focus on quality and flexibility, to a focus on speed and innovativeness.This was why it was interesting and important to research and discuss product development and especially to understand high speed product development of individualized products in fragile market segments. Consequently, findings and learning on aspects like enablers, management tools, technological tools, product development models, product development processes and network tools to speed new product development are presented in this book.